Modified carbon nanotube, antistatic silicone rubber and preparation method

By modifying carbon nanotubes using a modified carbon nanotube preparation method, carbon nanotubes are modified with methyl vinyl silicone rubber raw rubber and ionic liquid, and combined with grinding treatment, the problems of dispersion and interfacial bonding of carbon nanotubes in silicone rubber are solved, thereby improving antistatic properties and mechanical fatigue properties.

CN121673648APending Publication Date: 2026-03-17GUANGZHOU SIYOU NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610101050.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-26
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

In the prior art, carbon nanotubes have poor dispersion and interfacial bonding in silicone rubber, resulting in low and unstable conductive network efficiency, making it difficult to maintain antistatic properties under dynamic mechanical stress.

Method used

Carbon nanotubes were modified using methyl vinyl silicone rubber raw material, 1-ethyl-3-methylimidazolium diethyl phosphate, and 1-ethyl-3-methylimidazolium ethyl sulfate. Stable conductive pathways were formed by winding and encapsulating the carbon nanotubes with high molecular weight methyl vinyl silicone rubber raw material, combined with grinding treatment.

Benefits of technology

This method achieves uniform dispersion and stable connection of carbon nanotubes in silicone rubber, improves the antistatic properties and mechanical fatigue properties of antistatic silicone rubber, and ensures that the conductive network remains stable under dynamic stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a modified carbon nanotube, antistatic silicone rubber and a preparation method. The modified carbon nano tube provided by the invention comprises the following components in parts by weight: 100 parts of methyl vinyl silicone rubber raw rubber, 5-25 parts of carbon nano tube, 3-7 parts of 1-ethyl-3-methylimidazole diethyl phosphate and 1-5 parts of 1-ethyl-3-methylimidazole ethyl sulfate, wherein the molecular weight of the raw methyl vinyl silicone rubber is 70-120 million, and the content of vinyl is 0-0.03%. When the modified carbon nanotube is used for preparing the antistatic silica gel, the obtained antistatic silica gel has excellent antistatic performance and heat resistance, and the mechanical fatigue performance is well maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rubber material preparation technology, and in particular to a modified carbon nanotube, an antistatic silicone rubber, and a preparation method thereof. Background Technology

[0002] Silicone rubber is widely used in electronics, medical devices, automotive, and aerospace industries due to its excellent high and low temperature resistance, superior electrical insulation properties, good physiological inertness, and weather resistance. However, its inherently extremely high volume resistivity (typically higher than 1×10¹) is a significant drawback. 5 The high resistance (Ω·cm) of silicone rubber products makes them prone to static charge accumulation in dry environments. This can lead to problems such as dust attraction and discharge interference, and poses potential safety risks in precision electronics, flammable and explosive environments. Therefore, there is an urgent market demand for silicone rubber materials with durable and stable antistatic properties. To impart conductivity to silicone rubber, the industry commonly uses the addition of conductive fillers. Traditional fillers such as carbon black and metal powders can reduce resistance, but often require very high addition amounts (usually exceeding 20%) to form an effective conductive permeation network. High filler content severely degrades the inherent mechanical properties of silicone rubber, such as flexibility and tensile strength, and worsens its processing performance, limiting its use in applications requiring the maintenance of rubber elasticity and flexibility.

[0003] Carbon nanotubes, with their extremely high aspect ratio and excellent intrinsic conductivity, are considered ideal fillers for preparing lightweight, high-performance conductive polymer composites. However, directly applying carbon nanotubes to silicone rubber systems faces significant challenges: First, the high surface energy and strong van der Waals forces of carbon nanotubes make them prone to aggregation in non-polar silicone rubber matrices, hindering uniform dispersion and resulting in inefficient and unstable conductive networks. Second, and more critically, even if initial dispersion is achieved through strong shearing, the carbon nanotube network is highly susceptible to slippage and breakage due to weak interfacial bonding during subsequent processing (such as repeated milling) or actual use, especially when the silicone rubber matrix is ​​subjected to dynamic mechanical stress (such as bending and kneading). This disrupts the conductive pathways and significantly reduces antistatic properties. Existing technologies often employ surface modification with silane coupling agents to improve the dispersibility and interfacial bonding of carbon nanotubes. However, these methods tend to focus on improving static dispersibility and initial conductivity, offering limited effectiveness in addressing the long-term stability of conductive networks under dynamic mechanical fatigue and thermal aging conditions. Summary of the Invention

[0004] In view of the above, one object of the present invention is to provide a modified carbon nanotube. Another object of the present invention is to provide a method for preparing a modified carbon nanotube. A further object of the present invention is to provide an antistatic silicone rubber. A still other object of the present invention is to provide a method for preparing an antistatic silicone rubber.

[0005] The present invention achieves the above-mentioned technical objectives through the following technical solutions.

[0006] In a first aspect, the present invention provides a modified carbon nanotube comprising the following components: 100 parts by weight of methyl vinyl silicone rubber raw material, 5-25 parts by weight of carbon nanotubes, 3-7 parts by weight of 1-ethyl-3-methylimidazolium diethyl phosphate, and 1-5 parts by weight of 1-ethyl-3-methylimidazolium sulfate; wherein the methyl vinyl silicone rubber raw material has a molecular weight of 700,000 to 1,200,000 and a vinyl content of 0-0.03%.

[0007] The modified carbon nanotubes of this invention mainly comprise methyl vinyl silicone rubber raw material, carbon nanotubes, 1-ethyl-3-methylimidazolium diethyl phosphate, and 1-ethyl-3-methylimidazolium ethyl sulfate. Preferably, the methyl vinyl silicone rubber raw material is methyl-terminated; the amount of methyl vinyl silicone rubber raw material is 100 parts by weight. Based on 100 parts by weight of methyl vinyl silicone rubber raw material, the amount of carbon nanotubes can be 5-25 parts by weight, preferably 8-20 parts by weight, more preferably 10-15 parts by weight; the amount of 1-ethyl-3-methylimidazolium diethyl phosphate can be 3-7 parts by weight, preferably 4-7 parts by weight, more preferably 4-5 parts by weight; the amount of 1-ethyl-3-methylimidazolium ethyl sulfate can be 1-5 parts by weight, preferably 2-4 parts by weight, more preferably 2-3 parts by weight. The molecular weight of the methyl vinyl silicone rubber raw material is preferably 700,000-1,200,000, and the vinyl content is 0-0.03%. The combination of 1-ethyl-3-methylimidazolium diethyl phosphate and 1-ethyl-3-methylimidazolium ethyl sulfate may achieve more effective penetration and unwinding of carbon nanotubes through different polarities, steric hindrance, or surface energy matching. Using high molecular weight methyl vinyl silicone rubber as the masterbatch matrix, its long-chain molecules can effectively entangle and encapsulate the carbon nanotubes initially treated with 1-ethyl-3-methylimidazolium diethyl phosphate and 1-ethyl-3-methylimidazolium ethyl sulfate. Through physical adsorption and entanglement, stable conductive pathways are formed, creating solid functional units encapsulated and protected by silicone rubber.

[0008] According to the modified carbon nanotubes of the present invention, preferably, the carbon nanotubes are selected from single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

[0009] In this invention, single-walled carbon nanotubes possess higher intrinsic conductivity and aspect ratio, which is beneficial for constructing efficient conductive networks; multi-walled carbon nanotubes are lower in cost and have better processing tolerance. Depending on the comprehensive requirements of the final product for conductivity, mechanical properties, and cost, a single type of carbon nanotube can be selected, or the two can be combined in any proportion. This leverages the synergistic effect of the high performance of single-walled carbon nanotubes and the robustness of multi-walled carbon nanotubes to achieve comprehensive material performance.

[0010] The modified carbon nanotubes according to the present invention preferably comprise the following components: 100 parts by weight of methyl vinyl silicone rubber raw rubber, 8-20 parts by weight of carbon nanotubes, 4-7 parts by weight of 1-ethyl-3-methylimidazolium diethyl phosphate, and 2-4 parts by weight of 1-ethyl-3-methylimidazolium sulfate; wherein the molecular weight of the methyl vinyl silicone rubber raw rubber is 800,000 to 1,200,000, and the vinyl content is 0-0.03%.

[0011] Secondly, the present invention provides a method for preparing modified carbon nanotubes, comprising the following steps: S1: Heat the premixed and dried carbon nanotube powder to 100-150℃, and then slowly add 1-ethyl-3-methylimidazolium diethyl phosphate and 1-ethyl-3-methylimidazolium ethyl sulfate under stirring. After the addition is complete, continue stirring for 35-60 minutes to obtain the first mixture. S2: The first mixture is mixed and stirred with methyl vinyl silicone rubber raw material, and then ground to obtain modified carbon nanotubes.

[0012] In step S1, the premixed and dried carbon nanotube powder is first modified. The heating temperature can be 100–150°C, preferably 110–140°C, and more preferably 120–130°C. This improves fluidity, making it easier for the powder to penetrate into the tightly packed aggregates of carbon nanotubes, achieving uniform coating from the inside out. When the temperature is below 100°C, the fluidity of the ionic liquid may be insufficient, resulting in low modification efficiency. When the temperature is above 150°C, prolonged heating may increase the risk of oxidation or slight decomposition, and also increase energy consumption. The slow dropwise addition method ensures that the carbon nanotube powder is gradually wetted by the ionic liquid, which is beneficial for the ionic liquid to penetrate from the outer layer to the inner layer of the carbon nanotube bundle, maximizing the coating efficiency and avoiding external overload while the inside remains unmodified. The stirring time can be 35–60 min, preferably 40–55 min, and more preferably 45–50 min. This allows the ionic liquid to reach adsorption equilibrium on the surface of the carbon nanotubes, and with the synergistic effect of heat and shear, the coating layer becomes more uniform and stable. If the time is too short, the adsorption may be insufficient; if the time is too long, the performance improvement will not be significant and energy consumption will increase. At the same time, under continuous thermal stirring, the ionic liquid molecules adsorbed on the surface of carbon nanotubes can undergo orientation adjustment and spread, forming a denser and more ordered coating layer.

[0013] In step S2, mixing and stirring the first mixture with the methyl vinyl silicone rubber raw material allows the long-chain silicone rubber molecules to initially entangle and encapsulate the carbon nanotubes modified by the ionic liquid. Then, high shear force is applied through grinding to completely break up the agglomerations. Grinding can be done using a three-roll mill, ball mill, or similar equipment to generate enormous shear and extrusion forces, breaking up any remaining agglomerates of carbon nanotubes and achieving a primary or even secondary dispersion. Simultaneously, under the action of shear force, the carbon nanotubes, the ionic liquid coating layer, and the silicone rubber raw material are mixed, compressed, and stretched, greatly increasing the contact area and promoting physical fusion and interpenetration at the interfaces. After grinding, the resulting modified carbon nanotubes are easier to mix with the main rubber and can withstand shear damage during secondary processing, maintaining the stability of the dispersion.

[0014] The method for preparing modified carbon nanotubes according to the present invention preferably further includes drying the carbon nanotubes; the processing step is: vacuum drying the carbon nanotubes at 60~80℃ for 1~2h to obtain the premixed dried carbon nanotube powder.

[0015] In this invention, drying the carbon nanotube powder removes adsorbed moisture from its surface. The presence of moisture hinders the direct and effective contact between the ionic liquid and the carbon nanotube surface, leading to uneven subsequent modification and vaporization during high-temperature processing and use, potentially damaging the structural and performance stability of the composite material. Vacuum drying at 60-80°C achieves thorough dehydration of the carbon nanotubes under gentle conditions, while avoiding damage caused by high-temperature oxidation.

[0016] Thirdly, the present invention also provides an antistatic adhesive comprising the following components: 100 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw rubber, 30-60 parts by weight of silica, 2-8 parts by weight of structure control agent, 0.1-0.5 parts by weight of release agent, 1-1.5 parts by weight of vulcanizing agent, and 5-15 parts by weight of the modified carbon nanotubes mentioned above; wherein the vinyl-terminated methyl vinyl silicone rubber raw rubber has a molecular weight of 500,000-700,000 and a vinyl content of 0.04-0.23%.

[0017] The antistatic silicone rubber of the present invention comprises vinyl-terminated methyl vinyl silicone rubber raw material, silica, a structure control agent, a release agent, a vulcanizing agent, and modified carbon nanotubes as described above. Based on 100 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw material, the amount of silica can be 30-60 parts by weight, preferably 35-50 parts by weight, more preferably 35-45 parts by weight. The amount of the structure control agent can be 2-8 parts by weight, preferably 3.5-6.5 parts by weight, more preferably 4-6 parts by weight. The amount of the release agent can be 0.1-0.5 parts by weight, preferably 0.2-0.45 parts by weight, more preferably 0.35-0.4 parts by weight. The amount of the modified carbon nanotubes can be 5-15 parts by weight, preferably 7.5-10 parts by weight, more preferably 8.5-9.5 parts by weight. Based on the total weight of the vinyl-terminated methyl vinyl silicone rubber raw material, silica, structure control agent, release agent and modified carbon nanotubes, the amount of vulcanizing agent can be 1 to 1.5 parts by weight, preferably 1.1 to 1.4 parts by weight, and more preferably 1.15 to 1.32 parts by weight.

[0018] In this invention, vinyl-terminated methyl vinyl silicone rubber raw material with a molecular weight of 500,000 to 700,000 and a vinyl content of 0.04% to 0.23% is selected as the matrix to obtain a continuous rubber phase with suitable mechanical strength, high elasticity, and stable cross-linking structure while ensuring good processing performance of the rubber compound. This continuous phase can provide a robust yet flexible support for the conductive network constructed by modified carbon nanotubes, ensuring the antistatic and heat resistance of the composite material, and maintaining good mechanical fatigue resistance.

[0019] In this invention, a structure control agent is used to assist in the dispersion of carbon nanotubes and prevent structuring. The structure control agent may be selected from at least one of hydroxyl silicone oil, silazane, alkoxysilane, and their oligomers, preferably from hydroxyl silicone oil or silazane, and more preferably from hydroxyl silicone oil. The release agent may be selected from at least one of fatty acids and their metal salts, fatty acid esters, and polysiloxanes, preferably from fatty acids and their metal salts or fatty acid esters, and more preferably from fatty acids and their metal salts, such as stearic acid and zinc stearate. The vulcanizing agent decomposes under heating conditions to generate free radicals, initiating a cross-linking reaction between the raw silicone rubber molecules to form a three-dimensional network structure. The vulcanizing agent is preferably a peroxide vulcanizing agent, such as benzoyl peroxide, bis-2,4-dichlorobenzoyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, and 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane.

[0020] According to the antistatic adhesive of the present invention, preferably, the vinyl-terminated methyl vinyl silicone rubber raw rubber is a composition of vinyl-terminated methyl vinyl silicone rubber raw rubber A and vinyl-terminated methyl vinyl silicone rubber raw rubber B; wherein the mass ratio of the vinyl-terminated methyl vinyl silicone rubber raw rubber A to the vinyl-terminated methyl vinyl silicone rubber raw rubber B is 50-80:20-50.

[0021] In this invention, two raw rubbers, A and B, with significantly different vinyl content, are compounded to construct a rubber matrix with a gradient crosslinking density. Raw rubber A, with a low vinyl content, forms a flexible continuous phase, imparting the material with extremely high elasticity and deformation capacity; raw rubber B, with a high vinyl content, acts as a rigid reinforcing phase, providing the necessary mechanical strength. The two are combined in a specific ratio to synergistically form a composite matrix that combines rigidity and flexibility. The mass ratio of vinyl-terminated methyl vinyl silicone rubber raw rubber A to vinyl-terminated methyl vinyl silicone rubber raw rubber B is 50–80:20–50, preferably 60–80:20–40, and more preferably 70–75:25–30. This matrix not only possesses excellent resistance to mechanical fatigue but also provides a stable environment for the modified carbon nanotube conductive network. This ensures that the antistatic silicone rubber obtained in this invention maintains a highly stable structure even after repeated dynamic stress.

[0022] According to the antistatic adhesive of the present invention, preferably, the vinyl content in the vinyl-terminated methyl vinyl silicone rubber raw material A is 0.04-0.06%, and the vinyl content in the vinyl-terminated methyl vinyl silicone rubber raw material B is 0.15-0.24%.

[0023] In this invention, when the vinyl content of raw rubber A is controlled within a specific range of 0.04–0.06% and the vinyl content of raw rubber B is controlled within a specific range of 0.15–0.24%, and they are compounded in the aforementioned ratio, an unexpected synergistic effect can be achieved. Raw rubber A with low vinyl content forms a continuous soft phase, imparting extreme elasticity to the matrix; raw rubber B with high vinyl content acts as a dispersed hard phase, providing rigid support. This 'soft-hard' combined gradient network not only possesses excellent resistance to mechanical fatigue, but more importantly, it provides an ideal microenvironment for the modified carbon nanotube conductive network, combining 'flexible buffering' and 'rigid anchoring'. This ensures that the antistatic silicone rubber obtained in this invention maintains a highly stable conductivity even after undergoing dynamic mechanical action.

[0024] Fourthly, the present invention also provides a method for preparing antistatic silicone rubber, comprising the following steps: S1: First, the vinyl-terminated methyl vinyl silicone rubber raw material, release agent, structure control agent, and fumed silica are kneaded and mixed to form a uniformly mixed masterbatch; then, the masterbatch is kept at 120-180℃ for 100-150 minutes to obtain silicone rubber masterbatch. S2: After the temperature of the silicone rubber masterbatch drops to room temperature, the silicone rubber masterbatch, modified carbon nanotubes and vulcanizing agent are fed into a two-roll mill for refining to obtain antistatic silicone rubber.

[0025] In step S1 of this invention, the mixing temperature can be 120–180°C, preferably 130–170°C, and more preferably 140–160°C. The mixing time can be 100–150 min, preferably 110–140 min, and more preferably 120–130 min. This allows the silica to achieve optimal dispersion and bonding in the matrix, constructing a strong and tough matrix. Further mixing after cooling effectively avoids the damage to the thermosensitive ionic liquid function and the pre-constructed carbon nanotube conductive network caused by high temperature and strong shear, ensuring the integrity of the conductive function. Finally, the vulcanizing agent is added at a low temperature to prevent scorching and ensure uniform vulcanization, guaranteeing that the composite material of this invention simultaneously obtains excellent antistatic and mechanical properties.

[0026] The method for preparing antistatic silicone rubber according to the present invention preferably further includes molding the antistatic silicone rubber; the molding temperature is 160-180°C and the molding time is 10-15 min.

[0027] In this invention, the molding temperature can be 160–180°C, preferably 170–175°C. The molding time can be 10–15 min, preferably 10–12 min. This temperature range ensures efficient decomposition of the selected peroxide vulcanizing agent, achieving full cross-linking of the silicone rubber matrix, while also strictly controlling it within the thermal stability window of the ionic liquid to avoid functional failure. This time range is sufficient to reach the positive vulcanization point, obtaining optimal mechanical and elastic properties, while preventing embrittlement caused by over-vulcanization and potential damage to the conductive network from prolonged thermal exposure.

[0028] In summary, this application includes at least one of the following beneficial technical effects: (1) The modified carbon nanotubes of the present invention use high molecular weight methyl vinyl silicone rubber raw rubber as the masterbatch matrix. Its long-chain molecules can effectively entangle and encapsulate the carbon nanotubes that have been pre-treated with 1-ethyl-3-methylimidazolium diethyl phosphate and 1-ethyl-3-methylimidazolium ethyl sulfate. Through physical adsorption and entanglement, a stable conductive pathway is formed and a solid functional unit is encapsulated and protected by silicone rubber. Such modified carbon nanotubes are used in the preparation of antistatic silicone rubber, and the resulting antistatic silicone rubber has excellent antistatic properties and heat resistance, and maintains good mechanical fatigue properties.

[0029] (2) The preparation method of the present invention is simple and easy to implement. Detailed Implementation

[0031] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0032] The main raw materials used in the examples are from the following sources: (1) Methyl-terminated methyl vinyl silicone rubber raw rubber: Model 101, molecular weight 1.1 million, vinyl content 0%, Yichang Xingyue New Materials Co., Ltd.; (2) Single-walled carbon nanotubes: TUBALL™, Occidental; (3) Multi-walled carbon nanotubes: FT9000, Jiangsu Tiannai Technology Co., Ltd.; (4) 1-Ethyl-3-methylimidazolium diethyl phosphate: Maclean; (5) 1-Ethyl-3-methylimidazolium sulfate ethyl ester: Maclean; (6) Vinyl-terminated methyl vinyl silicone rubber raw material A: 110-0, Hoshine Silicon Industry Co., Ltd.; (7) Vinyl-terminated methyl vinyl silicone rubber raw material B: 110-3, Hoshine Silicon Industry Co., Ltd.; (8) Silica: HL-200, Hubei Huifu Nanomaterials Co., Ltd.; (9) Hydroxyl silicone oil: 207-30, Zhejiang Zhenghe Silicon Materials; (10) Zinc stearate: SAK-ZS-PLB, San Yi Chemical, Singapore; (11) 2,5-Dimethyl-2,5-bis(tert-butylperoxy)hexane: Trigonox 101, AkzoNobel; (12) Vinyl-terminated methyl vinyl silicone oil: Hoshine Silicon Industry Co., Ltd.; (13) Polyethylene glycol 400: Sigma-Aldrich (Shanghai) Trading Co., Ltd.

[0033] Preparation Example 1 Single-walled carbon nanotubes and multi-walled carbon nanotubes were vacuum dried at 80°C for 1 hour to obtain premixed dried carbon nanotube powder. 5 parts by weight of the premixed dried single-walled carbon nanotube powder and 15 parts by weight of the premixed dried multi-walled carbon nanotubes were heated to 120°C, and then 7 parts by weight of 1-ethyl-3-methylimidazolium diethyl phosphate and 3 parts by weight of 1-ethyl-3-methylimidazolium sulfate were slowly added dropwise under stirring. After the addition was complete, stirring was continued for 45 minutes to obtain the first mixture. The first mixture was mixed and stirred with 100 parts by weight of methyl-terminated methyl vinyl silicone rubber raw material, and then ground to obtain modified carbon nanotubes.

[0034] Preparation Example 2 Multi-walled carbon nanotubes were vacuum dried at 80°C for 1 hour to obtain premixed dried carbon nanotube powder. 15 parts by weight of the premixed dried multi-walled carbon nanotube powder were heated to 120°C, and then 5 parts by weight of 1-ethyl-3-methylimidazolium diethyl phosphate and 2 parts by weight of 1-ethyl-3-methylimidazolium sulfate were slowly added dropwise under stirring. After the addition was completed, stirring was continued for 45 minutes to obtain the first mixture. The first mixture was mixed and stirred with 100 parts by weight of methyl-terminated methyl vinyl silicone rubber raw material (same as in Preparation Example 1), and then ground to obtain modified carbon nanotubes.

[0035] Preparation Example 3 Single-walled carbon nanotubes and multi-walled carbon nanotubes were vacuum dried at 80°C for 1 hour to obtain premixed dried carbon nanotube powder. Six parts by weight of the premixed dried single-walled carbon nanotube powder and eight parts by weight of the premixed dried multi-walled carbon nanotubes were heated to 120°C, and then five parts by weight of 1-ethyl-3-methylimidazolium diethyl phosphate and two parts by weight of 1-ethyl-3-methylimidazolium sulfate were slowly added dropwise under stirring. After the addition was completed, stirring was continued for 45 minutes to obtain the first mixture. The first mixture was mixed and stirred with 100 parts by weight of methyl-terminated methyl vinyl silicone rubber raw material (same as in Preparation Example 1), and then ground to obtain modified carbon nanotubes.

[0036] Preparation Example 4 Single-walled carbon nanotubes were vacuum dried at 80°C for 1 hour to obtain premixed dried carbon nanotube powder. 15 parts by weight of the premixed dried single-walled carbon nanotube powder were heated to 120°C, and then 5 parts by weight of 1-ethyl-3-methylimidazolium diethyl phosphate and 2 parts by weight of 1-ethyl-3-methylimidazolium sulfate were slowly added dropwise under stirring. After the addition was completed, stirring was continued for 45 minutes to obtain the first mixture. The first mixture was mixed and stirred with 100 parts by weight of methyl-terminated methyl vinyl silicone rubber raw material (same as in Preparation Example 1), and then ground to obtain modified carbon nanotubes.

[0037] Preparation Example 5 Single-walled carbon nanotubes were vacuum dried at 80°C for 1 hour to obtain premixed dried carbon nanotube powder. 25 parts by weight of the premixed dried single-walled carbon nanotube powder were heated to 120°C, and then 4 parts by weight of 1-ethyl-3-methylimidazolium diethyl phosphate and 4 parts by weight of 1-ethyl-3-methylimidazolium sulfate were slowly added dropwise under stirring. After the addition was completed, stirring was continued for 45 minutes to obtain the first mixture. The first mixture was mixed and stirred with 100 parts by weight of methyl-terminated methyl vinyl silicone rubber raw material (same as in Preparation Example 1), and then ground to obtain modified carbon nanotubes.

[0038] Preparation Example 6 Multi-walled carbon nanotubes were vacuum dried at 80°C for 1 hour to obtain premixed dried carbon nanotube powder. Eight parts by weight of the premixed dried multi-walled carbon nanotube powder were heated to 120°C, and then four parts by weight of 1-ethyl-3-methylimidazolium diethyl phosphate and four parts by weight of 1-ethyl-3-methylimidazolium sulfate were slowly added dropwise under stirring. After the addition was completed, stirring was continued for 45 minutes to obtain the first mixture. The first mixture was mixed and stirred with 100 parts by weight of methyl-terminated methyl vinyl silicone rubber raw material (same as in Preparation Example 1), and then ground to obtain modified carbon nanotubes.

[0039] Comparative Preparation Example 1 Replace the methyl-terminated methyl vinyl silicone rubber raw material with vinyl-terminated methyl vinyl silicone oil. The rest is the same as in Preparation Example 1.

[0040] Comparative Preparation Example 2 Except for replacing 7 parts by weight of 1-ethyl-3-methylimidazolium diethyl phosphate and 3 parts by weight of 1-ethyl-3-methylimidazolium ethyl sulfate with 10 parts by weight of polyethylene glycol 400, the rest is the same as in Preparation Example 1. Example 1

[0041] First, 100 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw A, 0.4 parts by weight of zinc stearate, 4 parts by weight of hydroxyl silicone oil, and 45 parts by weight of silica are kneaded and mixed in an internal mixer to form a uniformly mixed masterbatch; then the masterbatch is kept at 150°C for 120 minutes to obtain silicone rubber masterbatch.

[0042] After the temperature of the silicone rubber masterbatch is reduced to room temperature, the silicone rubber masterbatch, 8 parts by weight of the modified carbon nanotubes obtained in Preparation Example 1, and 1.26 parts by weight of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane are fed into a two-roll mill and milled for 35 rolls to obtain antistatic silicone rubber. Example 2

[0043] First, 85 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw material A, 15 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw material B, 0.4 parts by weight of zinc stearate, 3.5 parts by weight of hydroxyl silicone oil and 30 parts by weight of silica are kneaded and mixed in an internal mixer to form a uniformly mixed masterbatch; then the masterbatch is kept at 150°C for 120 minutes to obtain silicone rubber masterbatch.

[0044] After the temperature of the silicone rubber masterbatch is reduced to room temperature, the silicone rubber masterbatch, 10 parts by weight of the modified carbon nanotubes obtained in Preparation Example 1, and 1.15 parts by weight of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane are fed into a two-roll mill and milled for 35 rolls to obtain antistatic silicone rubber. Example 3

[0045] First, 50 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw material A, 50 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw material B, 0.4 parts by weight of zinc stearate, 5.5 parts by weight of hydroxyl silicone oil and 40 parts by weight of silica are kneaded and mixed in an internal mixer to form a uniformly mixed masterbatch; then the masterbatch is kept at 150°C for 120 minutes to obtain silicone rubber masterbatch.

[0046] After the temperature of the silicone rubber masterbatch is reduced to room temperature, the silicone rubber masterbatch, 8.5 parts by weight of the modified carbon nanotubes obtained in Preparation Example 1, and 1.24 parts by weight of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane are fed into a two-roll mill and milled for 35 rolls to obtain antistatic silicone rubber. Example 4

[0047] First, 75 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw material A, 25 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw material B, 0.4 parts by weight of zinc stearate, 6 parts by weight of hydroxyl silicone oil and 35 parts by weight of silica are kneaded and mixed in a mixer to form a uniformly mixed masterbatch; then the masterbatch is kept at 150°C for 120 minutes to obtain silicone rubber masterbatch.

[0048] After the temperature of the silicone rubber masterbatch is reduced to room temperature, the silicone rubber masterbatch, 7.5 parts by weight of the modified carbon nanotubes obtained in Preparation Example 1, and 1.19 parts by weight of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane are fed into a two-roll mill and milled for 35 rolls to obtain antistatic silicone rubber. Example 5

[0049] First, 100 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw material B, 0.4 parts by weight of zinc stearate, 8 parts by weight of hydroxyl silicone oil and 50 parts by weight of silica are kneaded and mixed in an internal mixer to form a uniformly mixed masterbatch; then the masterbatch is kept at 150°C for 120 minutes to obtain silicone rubber masterbatch.

[0050] After the temperature of the silicone rubber masterbatch is reduced to room temperature, the silicone rubber masterbatch, 15 parts by weight of the modified carbon nanotubes obtained in Preparation Example 1, and 1.39 parts by weight of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane are fed into a two-roll mill and milled for 35 rolls to obtain antistatic silicone rubber. Example 6

[0051] First, 65 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw material A, 35 parts by weight of vinyl-terminated methyl vinyl silicone rubber raw material B, 0.4 parts by weight of zinc stearate, 5 parts by weight of hydroxyl silicone oil and 50 parts by weight of silica are kneaded and mixed in an internal mixer to form a uniformly mixed masterbatch; then the masterbatch is kept at 150°C for 120 minutes to obtain silicone rubber masterbatch.

[0052] After the temperature of the silicone rubber masterbatch is reduced to room temperature, the silicone rubber masterbatch, 9.5 parts by weight of the modified carbon nanotubes obtained in Preparation Example 1, and 1.32 parts by weight of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane are fed into a two-roll mill and milled for 35 rolls to obtain antistatic silicone rubber. Example 7

[0053] Except for replacing the modified carbon nanotubes obtained in Preparation Example 1 with the modified carbon nanotubes obtained in Preparation Example 2, the rest is the same as in Example 6. Example 8

[0054] Except for replacing the modified carbon nanotubes obtained in Preparation Example 1 with the modified carbon nanotubes obtained in Preparation Example 3, the rest is the same as in Example 6. Example 9

[0055] Except for replacing the modified carbon nanotubes obtained in Preparation Example 1 with the modified carbon nanotubes obtained in Preparation Example 4, the rest is the same as in Example 6. Example 10

[0056] Except for replacing the modified carbon nanotubes obtained in Preparation Example 1 with the modified carbon nanotubes obtained in Preparation Example 5, the rest is the same as in Example 6. Example 11

[0057] Except for replacing the modified carbon nanotubes obtained in Preparation Example 1 with the modified carbon nanotubes obtained in Preparation Example 6, the rest is the same as in Example 6.

[0058] Comparative Example 1 Except for replacing the modified carbon nanotubes of Preparation Example 1 with the modified carbon nanotubes of Comparative Preparation Example 1, the rest is the same as in Example 4.

[0059] Comparative Example 2 Except for replacing the modified carbon nanotubes of Preparation Example 1 with the modified carbon nanotubes of Comparative Preparation Example 2, the rest were the same as in Example 4.

[0060] Comparative Example 3 The modified carbon nanotubes were replaced with ordinary multi-walled carbon nanotubes, and the rest was the same as in Example 4.

[0061] The properties of the antistatic silicone rubbers in Examples 1-11 and Comparative Examples 1-3 were tested using the following methods: Taking Example 1 as an example, after the raw material is refined 35 times, two samples are taken and placed into molds (12.5 cm × 12.5 cm × 2 mm) and molded in a molding machine (molding temperature is 170°C, molding time is 10 min) to obtain two antistatic silicone rubber test pieces. The resistance of one antistatic silicone rubber test piece is tested to obtain the initial resistance value. Then it is placed in an oven at 300°C for 24 hours and taken out to cool naturally to room temperature to test the surface resistance. The other antistatic silicone rubber test piece is folded in half and repeatedly rubbed in the hand for 1 min before testing the resistance. The remaining sample in the open mill is refined 100 times, and a portion is taken out and pressed into a test piece to test its resistance. The remaining sample in the open mill is then refined again, and a test piece is pressed and tested for resistance after every additional 100 refinements, until 300 refinements are completed.

[0062] The testing methods for the other embodiments and comparative examples are similar.

[0063] The test results are shown in Table 1.

[0064]

[0065] As shown in Table 1, the resistance of the antistatic silicone rubbers in Examples 1 to 11 is all within 10 ohms. 6 ~10 9 Between Ω, it exhibits excellent antistatic properties, and the resulting silicone rubber retains a resistance of 10 Ω after repeated grinding (300 cycles). 7 ~10 8 The resistance remained at the Ω level without significant attenuation, indicating stable antistatic properties. After aging at 300℃ for 24 hours, no significant attenuation was observed, indicating good heat resistance. After rubbing, the resistance showed only a slight increase, indicating a stable conductive network structure and good performance retention after mechanical fatigue.

[0066] In Comparative Example 1, after replacing the methyl-terminated methyl vinyl silicone rubber with vinyl-terminated methyl vinyl silicone oil, the antistatic properties remained at 10 ohms in both the initial and 100 open-mill cycles. 6 ~10 9The resistance was between Ω, but increased significantly after 300 cycles, indicating unstable antistatic properties. The resistance was very high after rubbing, indicating poor performance retention after mechanical fatigue. After aging at 300℃ for 24 hours, the resistance also increased, indicating weaker heat resistance compared to the antistatic silicone rubber of this application. This may be because, in the preparation of the modified carbon nanotubes, replacing the methyl-terminated methyl vinyl silicone rubber raw material with vinyl-terminated methyl vinyl silicone oil altered the chemical stability and interfacial properties of the masterbatch, hindering the uniform construction and flexible connection of the conductive network, thus affecting the antistatic properties. Under repeated stress, stress concentration easily occurs at the interface, accelerating the debonding of the carbon nanotubes from the matrix, leading to rapid failure of the conductive network and affecting the retention of mechanical fatigue properties.

[0067] In Comparative Example 2, replacing the composite ionic liquid with polyethylene glycol 400 altered the thermal stability, chemical stability, and interaction mechanism with carbon nanotubes and silicone rubber raw materials of the ionic liquid. The heat resistance decreased significantly, and the performance remained poor after mechanical fatigue. Although it could maintain a certain level of antistatic properties initially, the antistatic properties also showed a downward trend after 300 open milling cycles.

[0068] In Comparative Example 3, when ordinary carbon nanotubes were used, the carbon nanotubes may have agglomerated in the silicone rubber matrix due to the lack of modification, making it difficult to disperse uniformly. This resulted in low and unstable conductive network efficiency, leading to a significant decline in performance across all aspects.

[0069] This invention is not limited to the above-described embodiments. Any modifications, improvements, or substitutions that can be conceived by those skilled in the art without departing from the essential content of this invention fall within the scope of this invention.

Claims

1. A modified carbon nanotube, characterized by, The composition comprises the following components: 100 parts by weight of methyl vinyl silicone rubber crude rubber, 5-25 parts by weight of carbon nanotubes, 3-7 parts by weight of 1-ethyl-3-methyl imidazole diethyl phosphate and 1-5 parts by weight of 1-ethyl-3-methyl imidazole ethyl sulfate; wherein the molecular weight of the methyl vinyl silicone rubber crude rubber is 700-1200 thousand, and the content of vinyl is 0-0.03%.

2. The modified carbon nanotube of claim 1, wherein The carbon nanotubes are selected from single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

3. The modified carbon nanotube of claim 1, wherein, The composition comprises the following components: 100 parts by weight of methyl vinyl silicone rubber crude rubber, 8-20 parts by weight of carbon nanotubes, 4-7 parts by weight of 1-ethyl-3-methyl imidazole diethyl phosphate and 2-4 parts by weight of 1-ethyl-3-methyl imidazole ethyl sulfate; wherein the molecular weight of the methyl vinyl silicone rubber crude rubber is 800-1200 thousand, and the content of vinyl is 0-0.03%.

4. A method for producing the modified carbon nanotube according to any one of claims 1 to 3, characterized by, The method comprises the following steps: S1: heating the premixed dry carbon nanotube powder to 100-150 DEG C, then slowly adding 1-ethyl-3-methyl imidazole diethyl phosphate and 1-ethyl-3-methyl imidazole ethyl sulfate under stirring, and continuing to stir for 35-60 min after the addition to obtain a first mixture; S2: mixing the first mixture with methyl vinyl silicone rubber crude rubber, and then grinding to obtain modified carbon nanotubes.

5. The method of claim 3, wherein the carbon nanotubes are modified by the reaction of the carbon nanotubes with the oxidizing agent and the reducing agent. The method further comprises drying the carbon nanotubes; the drying step is: vacuum drying the carbon nanotubes at 60-80 DEG C for 1-2 h to obtain the premixed dry carbon nanotube powder.

6. An antistatic silicone rubber, characterized by, The composition comprises the following components: 100 parts by weight of vinyl-terminated methyl vinyl silicone rubber crude rubber, 30-60 parts by weight of white carbon black, 2-8 parts by weight of a structure control agent, 0.1-0.5 parts by weight of a release agent, 1-1.5 parts by weight of a vulcanizing agent and 5-15 parts by weight of the modified carbon nanotubes according to any one of claims 1-3; wherein the molecular weight of the vinyl-terminated methyl vinyl silicone rubber crude rubber is 500-700 thousand, and the content of vinyl is 0.04-0.23%.

7. The antistatic silicone rubber according to claim 5, characterized in that, The vinyl-terminated methyl vinyl silicone rubber crude rubber is a combination of vinyl-terminated methyl vinyl silicone rubber crude rubber A and vinyl-terminated methyl vinyl silicone rubber crude rubber B; wherein the mass ratio of the vinyl-terminated methyl vinyl silicone rubber crude rubber A to the vinyl-terminated methyl vinyl silicone rubber crude rubber B is 50-80:20-50.

8. The antistatic silicone rubber according to claim 6, characterized in that, The content of vinyl in the vinyl-terminated methyl vinyl silicone rubber crude rubber A is 0.04-0.06%, and the content of vinyl in the vinyl-terminated methyl vinyl silicone rubber crude rubber B is 0.15-0.24%.

9. A process for the preparation of an antistatic silicone rubber according to any one of claims 6 to 8, characterized in that, The method comprises the following steps: S1: first kneading and mixing the vinyl-terminated methyl vinyl silicone rubber crude rubber, the release agent, the structure control agent and the white carbon black to form a uniformly mixed masterbatch; then keeping the masterbatch at a temperature of 120-180 DEG C for 100-150 min to obtain a silicone rubber masterbatch; S2: after the temperature of the silicone rubber masterbatch decreases to room temperature, feeding the silicone rubber masterbatch, the modified carbon nanotubes and the vulcanizing agent into an open mill to mill, and obtaining an antistatic silicone rubber.

10. The method of preparing an antistatic silicone rubber according to claim 9, characterized by, Also included is compression molding of the antistatic silicone rubber; the compression molding temperature is 160-180 DEG C, and the compression molding time is 10-15 minutes.